ELECTRIC CARS WITH HYDROGEN BATTERIES (TAMADDUN NURI JURNALI, 2024)
The growing demand for energy resources and the threat of exhaustion of the existing energy reserves show that it is necessary to create new energy resources that can replace them. Hydrogen is an alternative gas that can be used as an energy source. Using it instead of gasoline, gas (methane, propane) or electricity in cars leads to a reduction in environmental pollution, as well as saving the above resources (gasoline, gas and electricity).